2014
DOI: 10.1590/s0103-56652014000200012
|View full text |Cite
|
Sign up to set email alerts
|

Subjetividade contemporânea: narcisismo e estados afetivos em um grupo de adultos jovens

Abstract: Narcisismo em adultos jovens Subjetividade contemporânea: narcisismo e estados afetivos em um grupo de adultos jovens Contemporary subjeCtivity: narCissism and emotional states in a group of young adults subjetividad Contemporánea: narCisismo y estados afeCtivos en un grupo de jóvenes adultos

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 12 publications
3
3
0
1
Order By: Relevance
“…This result is 11.4% higher than the average NPI of the female gender (12.76). These averages are similar to those averages (men = 14.24/women = 11.74) observed in the study of Langaro and Benetti (2014). It's important to note that the scores in this study ranged from 1 (one) to 39 (thirty-nine) points.…”
Section: Data Analysis and Discussion Of Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…This result is 11.4% higher than the average NPI of the female gender (12.76). These averages are similar to those averages (men = 14.24/women = 11.74) observed in the study of Langaro and Benetti (2014). It's important to note that the scores in this study ranged from 1 (one) to 39 (thirty-nine) points.…”
Section: Data Analysis and Discussion Of Resultssupporting
confidence: 88%
“…From this perspective, in order to identify the narcissistic personality traits in a group of youngsters and adults, Langaro and Benetti (2014) conducted a study with the participation of 350 university students, aged between 18 and 30, living in a city in the northwestern region of Rio Grande do Sul, a Brazilian state; they were enrolled in academic programs from different areas of knowledge. By collecting sociodemographic data and application of the NPI, it was found that men had higher rates of narcissistic traits if compared to women; students at the age group 18-21 had higher results in the exhibitionism factor than students in the age group 22-25; a higher level of narcissism was noted in the students of the Exact Sciences than in those of the Human and Health Sciences.…”
Section: Theorymentioning
confidence: 99%
“…In the Brazilian setting, the studies on the theme have been primarily published in the areas of education and psychology, for example, the studies by Severiano (1999), Caixeta (2011), and Langaro and Benetti (2014, among others. Severiano (1999) sought to understand the relationships between narcissism and advertising and showed for Brazilian and Spanish college students the ideas conveyed by advertising predominate in those students that present more heightened traits of narcissism.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Finally, Langaro and Benetti (2014) analyzed characteristics of narcissism, depression, anxiety, desperation, and self-esteem in 350 young college adults. As a result, they obtained a positive correlation between narcissism and self-esteem, between anxiety and depression, and between depression and desperation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A HADS e a DASS-21, diferentemente do IBD e do IDATE, avaliam não apenas os sintomas de ansiedade, pois possuem categorias de respostas para mensurar também sinais de depressão (APÓSTOLO, MENDES, AZEVERO, 2006;GAMA et al, 2008;LANGARO;BENETTI, 2014;MICHOPOULOS et al, 2008). No entanto, alguns estudos que adotaram esses instrumentos para avaliar ansiedade e depressão não apresentaram os resultados em conceitos distintos, por exemplo, o de Shin et al (2012a), que utilizou o termo sofrimento psíquico para se referir a duas variáveis em seus resultados, e a pesquisa de Ferreira e Guerra (2014), na qual se aplicou apenas a subescala referente à depressão.…”
Section: Lesão Medular Ansiedade E Depressãounclassified